Pengaruh Pemberian Plant Catalyst dan Media Tanam Terhadap Pertumbuhan dan Produksi Bawang Rambut (Allium chinense G.Don): Respon of Plant Catalyst and Growing Medium on the Growth and Production of Allium chinense G. Don - Rustam Baraq Noor; Fajar Sidik (Universitas Widya Gama Mahakam, 2021)
This reseach is aim respons plant catalyst and growing medium on the growth and production of Allium chinense G. Don. In Implementation for four months from April to July 2021. Research sites Agroteknologi practice Universitas Widya Gama Mahakam K. H. Wahid Hasyim street, in Samarinda city.The research design used a randomized completely block design (RCBD) repeated three times. Plant catalyst four level and growing medium four. The first factor is Plant Catalyst 2006 (P) : P0 = without Plant Catalyst 2006 (Control), P1 = 1 g Plant Catalyst 2006 per liter of water, P2 = 1.5 g Plant Catalyst 2006 per liter of water, P3 = 2 g Plant Catalyst 2006 per liter of water and the second factor is the planting medium (M), namely: M0 = topsoil, M1 = topsoil + manure (3:1), M2 = topsoil + goad manure + husk charcoal (2:1:1), M3 = topsoil + goad manure + husk charcoal + compost (1:1:1:1). The results showed of plant Catalyst treatment non signifint and growing media treatment are higly significant. Effect on the number of leaves 28 DAP, 42 DAP, 56 DAP, 70 DAP, number of tubers 70 DAP, root length 70 DAP, and tuber wet weight 70 DAP. The best treatment is growing medium that is topsoil and goad manure (3:1). Recommendation to Use the ratio of soil and goat manure 3:1 for the cultivation of allium chinense